2013
DOI: 10.1186/1471-2407-13-254
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Serum Carcinoembryonic Antigen (CEA) in evaluating response to chemotherapy in patients with advanced non small-cell lung cancer: a prospective cohort study

Abstract: BackgroundHigh serum carcinoembryonic antigen (CEA) levels are an independent prognostic factor for recurrence and survival in patients with non-small cell lung cancer (NSCLC). Its role as a predictive marker of treatment response has not been widely characterized.Methods180 patients with advanced NSCLC (stage IIIB or Stage IV), who had an elevated CEA serum level (>10 ng/ml) at baseline and who had no more than one previous chemotherapy regimen, were included. CEA levels were measured after two treatment cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 32 publications
(43 reference statements)
4
53
0
Order By: Relevance
“…Brechot et al [27] also reported CEA level of 27.1 ± 72.7 and 109 ± 404 ng/ml for respectable and unrespectable patients of NSCLC respectively. Several other reports documented lower [28] or higher [29] values of CEA than the present study in discussion.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Brechot et al [27] also reported CEA level of 27.1 ± 72.7 and 109 ± 404 ng/ml for respectable and unrespectable patients of NSCLC respectively. Several other reports documented lower [28] or higher [29] values of CEA than the present study in discussion.…”
Section: Discussionsupporting
confidence: 50%
“…In another study, Arrieta et al [29] documented amean baseline CEA of 242.8 ng/ml. The high value of CEA reported by Arrieta et al could be attributed to the fact that the majority of the studied NSCLC patients (84.4%) were in stage IV.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…RECIST has good accuracy and objectivity and plays an important role in guiding clinical practice, and it is a common method in solid tumor clinical research (Bang et al, 2010). However, RECIST may be insufficient under certain circumstances, especially for patients who lack measurable lesions or who have lesions with edges that are difficult to confirm, such as malignant effusions, diffuse lymph node metastases, and bone metastases (Arrieta et al, 2013;Shimada et al, 2014). Erasmus et al (2003) used spiral CT to detect the size of 40 tumor lesions in 33 patients with lung cancer and found that the measurement results were often inconsistent with each other, which was likely to cause decreased accuracy in determining the treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Serum tumor markers are detected automatically by machines and are often used for patient follow-up and prognosis determination. Recent studies have revealed that changes in the levels of serum markers have some value in predicting treatment efficacy for a variety of malignant tumors, especially ovarian cancer, colorectal cancer, and lung cancer (Hanke et al, 2001;Guppy and Rustin, 2007;Kim et al, 2010;Arrieta et al, 2013).…”
mentioning
confidence: 99%